2010
DOI: 10.1038/msb.2010.55
|View full text |Cite
|
Sign up to set email alerts
|

A model of yeast cell‐cycle regulation based on multisite phosphorylation

Abstract: Multisite phosphorylation of CDK target proteins provides the requisite nonlinearity for cell cycle modeling using elementary reaction mechanisms.Stochastic simulations, based on Gillespie's algorithm and using realistic numbers of protein and mRNA molecules, compare favorably with single-cell measurements in budding yeast.The role of transcription–translation coupling is critical in the robust operation of protein regulatory networks in yeast cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
120
3
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(143 citation statements)
references
References 74 publications
7
120
3
2
Order By: Relevance
“…Mutation of phosphorylated serine and threonine residues to alanine is functionally similar to the dephosphorylated state (58). The clustering of 30 phosphosites in the Med15 C terminus suggested that combinatorial phosphorylation on multiple sites affect biological outcome (59,60) as was shown for cell cycle control (61) and for transcription regulation (62).…”
Section: Med15 Phosphosites Contribute To Suppression Of Stress-inducmentioning
confidence: 82%
“…Mutation of phosphorylated serine and threonine residues to alanine is functionally similar to the dephosphorylated state (58). The clustering of 30 phosphosites in the Med15 C terminus suggested that combinatorial phosphorylation on multiple sites affect biological outcome (59,60) as was shown for cell cycle control (61) and for transcription regulation (62).…”
Section: Med15 Phosphosites Contribute To Suppression Of Stress-inducmentioning
confidence: 82%
“…One is for the bistable switch motif described in Section 2. The other is a more complete cell cycle model of budding yeast involving multiple phosphorylation states that was recently developed by John Tyson's group (Barik et al 2010). …”
Section: Stochastic Modeling and Simulation Of Multistate Systemsmentioning
confidence: 99%
“…However, they failed to capture the intrinsic noise that is caused by the stochastic effects of the low copy numbers of some species. Recently Tyson's group developed a stochastic model for the budding yeast cell cycle by integrating several functional biochemical motifs (Barik et al 2010). These motifs are based on multiple site phosphorylation, which has been discovered to generate nonlinear dynamics (Qu et al 2003) and form bistable switches.…”
Section: Budding Yeast Cell Cycle Modelmentioning
confidence: 99%
“…abundance initiates mitosis whereas starvation triggers meiosis (Barik et al, 2010;Kaizu et al, 2010;Nachman et al, 2007;Piekarska et al, 2010). Budding yeast cells can choose between meiosis or mitosis initiation alternatively according to the available nutrients until an irreversible point called 'commitment point' (Simchen, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The available deterministic models can be categorised into two groups depending on their objectives: (1) cell cycle regulation focussed models, where the cell cycle is modelled and controlling mechanisms at checkpoints such as START, G1/S are studied by analysis (Barik et al, 2010;Tóth et al, 2007;Verdugo et al;Vinod et al, 2011); and (2) cell cycle's temporal organisation focussed models, which explain orderly progression of the cell cycle steps by the periodical activation and inactivation of the associated regulators (mainly Cdks and Cyclins) (Chen et al, 2004;Hong et al, 2012;Tyson and Novak, 2008).…”
Section: Introductionmentioning
confidence: 99%